2013
DOI: 10.1021/ef401198m
|View full text |Cite
|
Sign up to set email alerts
|

Fischer–Tropsch Synthesis Catalyzed by Solid Nanoparticles at the Water/Oil Interface in an Emulsion System

Abstract: Fischer–Tropsch synthesis (FTS) was carried out in a water/oil mixture medium, using a Ru catalyst supported on a multi-walled carbon nanotube/MgO–Al2O3 hybrid as a catalyst support. The nanohybrid particles at the water/oil interface facilitated and stabilized the formation of water-in-oil emulsion, giving rise to an oil/emulsion/water trilayer liquid structure. FTS occurred at the emulsion phase with much higher conversion rates than those in oil single-phase reactions, yielding products with Anderson–Schulz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 43 publications
1
34
0
1
Order By: Relevance
“…More recently, Resasco and co-workers published two new applications of nanohybrid catalysts for enhanced oil recovery (EOR) and Fischer-Tropsch synthesis of fuels. [83] On the one hand, in the former study, [83a] the authors reported a comparable performance to that currently obtained by the injection of benchmark surfactant and polymer solutions. Interestingly, the supported metal could act as both an oxidative and a reductive catalyst while simultaneously decreasing the interfacial tension and increasing the viscosity of the sweeping phase.…”
Section: Amphiphilic Catalysts For Cascade Reactionsmentioning
confidence: 55%
See 1 more Smart Citation
“…More recently, Resasco and co-workers published two new applications of nanohybrid catalysts for enhanced oil recovery (EOR) and Fischer-Tropsch synthesis of fuels. [83] On the one hand, in the former study, [83a] the authors reported a comparable performance to that currently obtained by the injection of benchmark surfactant and polymer solutions. Interestingly, the supported metal could act as both an oxidative and a reductive catalyst while simultaneously decreasing the interfacial tension and increasing the viscosity of the sweeping phase.…”
Section: Amphiphilic Catalysts For Cascade Reactionsmentioning
confidence: 55%
“…Interestingly, the supported metal could act as both an oxidative and a reductive catalyst while simultaneously decreasing the interfacial tension and increasing the viscosity of the sweeping phase. On the other hand, in the latter development,83b the authors used ruthenium supported over MWCNT/MgO–Al 2 O 3 as a catalyst to perform the Fischer–Tropsch synthesis of fuels at the w/o interface, leading to a three‐layered liquid structure (oil/emulsion/water). The hydrocarbons migrated to the top phase, while short alcohols remained at the bottom phase, facilitating the separation of the reaction products.…”
Section: Catalysis In Pickering Emulsions Stabilized By Catalytic mentioning
confidence: 99%
“…With the development of nanoparticles, Pickering emulsion has been widely studied 23,24 and applied to food, cosmetics, sewage treatment, and material preparation because of its great stability, large interfacial area, and easy recovery of stabilizers 25‐27 . Pickering emulsion is also an ideal catalytic platform for liquid heterogeneous reactions 28,29 . Zapata et al prepared water in oil emulsion stabilized by nanohybrid catalysts to promote the condensation and hydrogenation of biomass‐derived oxygenates 30 .…”
Section: Introductionmentioning
confidence: 99%
“…Interessanterweise konnte das Metall auf dem Trägermaterial sowohl als Oxidations‐ als auch als Reduktionsmittel dienen, wobei zugleich die Oberflächenspannung ab‐ und die Viskosität der Transportphase zunahm. In der zweiten Studie83b verwendeten die Autoren dann Ruthenium auf einem MWCNT/MgO‐Al 2 O 3 ‐Träger als Katalysator für die Fischer‐Tropsch‐Synthese von Kraftstoffen an der w/o‐Grenzfläche und erhielten einen Dreischichtaufbau von Flüssigkeiten (Öl/Emulsion/Wasser). Während die Kohlenwasserstoffe in die oberste Phase wanderten, blieben die kurzkettigen Alkohole in der untersten Phase, was die Abtrennung der Reaktionsprodukte erleichterte.…”
Section: Katalyse In Durch Amphiphile Katalytische Nanopartikel Stunclassified